PENERAPAN METODE FINITE STATE MACHINE (FSM) PADA GAME ROLE PLAYING GAME (RPG) INK JOURNEYS - Egha Pacsi Yudha Perdana; Sri Winarso Martyas Edi (Fakultas Teknologi Informasi, Universitas Kristen Satya Wacana, 2024)
Lately, folklore is no longer well known by many people. The abundance of entertainment available on the internet has replaced entertainment in the previous era, including folklore. The game